Case Report of Dandy-Walker Malformation and Noonan Syndrome - Correlation of prenatal findings with neonatal evaluations - Ladeiras,Rita (2022)
Abstract This article reports a case of Dandy-Walker malformation (DWM) and Noonan Syndrome (NS) diagnosed in a fetus at the second trimester. The association between DWM and NS is rare and prenatal diagnosis of DWM generally motivates a medical termination of pregnancy. This is the first clinical case reported of DWM associated with NS with PTPN11 gene mutations and this article allows to correlate prenatal findings with clinical and other neonatal evaluations. On the other hand, it highlights the importance of prenatal evaluation of DWM and it shows the best techniques in order to improve prenatal counseling.